Validated Stability Indicating Rp-Hplc and Hptlc Methods for the Determination of Zanamivir in Bulk and Pharmaceutical Formulation - C. H. Bhirud (Challenges and Advances in Pharmaceutical Research Vol. 9, 2022)
The objective of the present work is to develop a simple, precise, accurate, validated stability indicating RP-HPLC and HPTLC method for the determination of Zanamivir in bulk and capsule dosage form. The HPLC separation was achieved on Agilent TC C18 (2) 250 x 4.6 mm, 5 \(μ \) column using mobile phase composition of methanol - 0.02 M phosphate buffer, pH 5, 50:50 (V/V). The flow rate was kept constant at 1 ml/min at room temperature. At 230 nm, UV detection was used to quantify. Zanamivir had a retention time of 3.6 minutes. The result obtained with the detector response was found to be linear in the concentration range of 2-12 \(μ \)g/ml. The method employed TLC aluminium plates precoated with silica gel 60F-254 as the stationary phase. The solvent system consisted of Chloroform: methanol: acetic acid (4.5:0.5:0.3v/v) and then scanned .The system was found to give compact spot for Zanamivir (Rf value of 0.29 ± 0.02). The linear regression analysis data for the calibration plots showed good relationship with r2=0.9999 ± 0.0001 in the concentration range 500-3000 ng/spot. The linearity, range, precision, accuracy, detection, and quantitation limitations of the suggested techniques, as well as their analytical performance, were statistically validated. The suggested methods could successfully separate Zanamivir from its degradation products when it was subjected to various stress settings; as a result, they were regarded as effective stability-indicating techniques. It is concluded that this technique can be used for zanamivir dosage forms and bulk drug routine quality control.